Progressive Back Pain due to Aspergillus nidulans Vertebral Osteomyelitis in an Immunocompetent Patient: Surgical and Antifungal Management. (2nd July 2019) - Lyons, Mark K.; Neal, Matthew T.; Patel, Naresh P.; Vikram, Holenarasipur R.
Abstract : Case Report . Aspergillus osteomyelitis is a destructive and progressive infection that has been described both in immunosuppressed and in immunocompetent hosts. We describe a case of lumbar vertebral osteomyelitis in a 61-year-old immunocompetent patient due to Aspergillus nidulans that was successfully treated with a combination of extensive surgical debridement, spinal stabilization, and a prolonged course of antifungal therapy. Imaging demonstrated findings consistent with L3 discitis. The biopsy grew Aspergillus fungus and was treated with vorconizole. Imaging showed progressive destructive osteomyelitis at L3-L4. Patient underwent anterior L3 and L4 partial corpectomies, anterior interbody fusion L3-L5, and posterior T11-S2 pedicle screw and rod fixation. Antifungal treatment resulted in resolution of infection. Aspergillus markers remain negative. One year following definitive treatment, the patient's back pain remains resolved. Conclusion . Definitive surgical resection of the infection, spinal stabilization, and aggressive antifungal therapy were required to eradicate the infection.